2016
DOI: 10.1002/nop2.45
|View full text |Cite
|
Sign up to set email alerts
|

Effects of training on attitudes of psychiatric personnel towards patients who self‐injure

Abstract: BackgroundImproving attitudes of personnel towards self‐injurious patients leads to better working alliance and contributes to better patient outcomes. Previous research into the improvement of these attitudes has recorded the need for specific training in evidence‐based assessment and treatment of self‐injurious patients.AimThe current study describes the attitudes towards self‐injurious patients among psychiatric personnel. The study also evaluates the effect of a structured clinical training program on psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 53 publications
1
10
1
3
Order By: Relevance
“…There is evidence that practical training improves the confidence, attitudes, knowledge and practical skills of nurses to work with patients who self‐injure (Saunders et al ., 2012). Several authors recommend training to improve knowledge and attitudes of staff (Jeffery & Warm, 2002; Karman, Kool, Poslawsky, & van Meijel, 2015; Saunders et al ., 2012), which in turn contribute to more positive health outcomes for people who self‐injure (Tapola, Wahlström, & Lappalainen, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that practical training improves the confidence, attitudes, knowledge and practical skills of nurses to work with patients who self‐injure (Saunders et al ., 2012). Several authors recommend training to improve knowledge and attitudes of staff (Jeffery & Warm, 2002; Karman, Kool, Poslawsky, & van Meijel, 2015; Saunders et al ., 2012), which in turn contribute to more positive health outcomes for people who self‐injure (Tapola, Wahlström, & Lappalainen, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical knowledge and attitudes of staff towards those who self‐injure is likely to influence clinical practice and the experience of people who seek care following NSSI (Saunders, Hawton, Fortune, & Farrell, 2012). Research conducted in the United States and Finland with nurses, doctors, social workers and psychologists found that staff hold negative attitudes towards patients who self‐injure (Muehlenkamp et al ., 2013; Tapola, Wahlström, & Lappalainen, 2016) and may respond with hostility, frustration and anger (Rayner et al ., 2019). Reece (2005) explored the language of self‐injury using a grounded theory and found that nurses working with patients who self‐injure may view them as ‘needing too much time’ to contain the behaviour when there are other competing nursing care tasks (Reece, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In present study there is significant difference in mean scores on knowledge as the't' value obtained was higher than the tabulated value at 0.05 level of significance. So, it can be concluded that self-instructional module on knowledge regarding care of attempted suicide patients among staff nurses is effective 11 .…”
Section: Discussionmentioning
confidence: 97%
“…Nurses have clearly articulated their needs for greater knowledge and training to support persons who self-injure (Karman et al, 2015). Nurses who receive training on NSSI report less negative attitudes toward persons who self-injure (Tapola, Wahlström, & Lappalainen, 2016) as well as greater empathy, self-efficacy, reduced stigma, and delivering improved quality of care (McAllister, Billett, Moyle, & Zimmer-Gembeck, 2009; Thornicroft et al, 2016). Taken together, these findings suggest the importance of educational training in supporting improved care for persons who engage in NSSI and the need for a nonjudgmental, empathic approach.…”
Section: Knowledge Provision and Its Impact On Nurses’ Attitudes Towamentioning
confidence: 99%